Outcome of Transurethral resection of prostate in patient of chronic retention of urine due to Benign enlargement of prostate (Bangladesh Journal of Urology, 2026)
Background: Chronic urinary retention (CUR) due to benign enlargement of prostate (BEP) causes impaired detrusor function secondary to obstruction related changes in urinary bladder. The gold standard surgical treatment option for relieve of obstruction is Transurethral resection of prostate (TURP). However, in chronic retention of urine, there is chance of detrusor underactivity.Objective: The present study evaluated the outcome of TURP in patients of chronic retention of urine due to benign enlargement of prostate irrespective of detrusor activity.Methods: This observational study involves 26 patients of BEP with chronic retention of urine underwent TURP after 6 Weeks long initial perurethral catheterization in the Department of Urology, Bangladesh Medical University (BMU), Shahbagh, Dhaka. The postoperative outcomes were evaluated on the basis of international prostate symptoms score (IPSS), Quality of life (QoL) maximum flow rate (Qmax), post void residual urine (PVR), grading of upper tract dilatation, serum creatinine, urodynamic parameters such as detrusor pressure at maximum flow (PDdetQmax), bladder contractility index (BCI), bladder outflow obstruction index (BOOI) three months after TURP.Results: The mean age of the patients was 65.2 ± 6.5 years which ranged from 53-80 years. Three months after TURP, the median PVR significantly reduced to 75.0 [40.0, 145.0] ml from 394.0 [333.0, 516.0] ml. Before TURP, 38% of patient had upper tract dilatation (UTD) among them, UTD decreases in 60% patient and 40% became normal. The median Qmax significantly increased to 18.2 [12.1, 22.1] ml/sec from 7.9 [5.6, 10.2] ml/sec. The median serum creatinine significantly reduced to 1.21 [0.91, 2.24] from preoperative 1.27 [0.95, 2.25]mg/dl. Median PdetQmax was significantly reduced to 49.3 [45.9, 53.7] from 88.1 [59.3, 106.2] after TURP. The median BCI increased to 151.6 [139.0, 167.2] from 136.1 [91.9, 154.5]. The median BOOI significantly reduced to 15.9 [8.0, 22.0] from 72.1 [44.1, 88.1].The median IPSS significantly reduced to 8.0 [6.7, 10.0] from 20.0 [15.0, 25.0] while median QoL was also significantly reduced to 2.0 [2.0, 2.0] from 4.0 [4.0, 4.2]. Among the 8 patients, having hypocontractile bladder, 2 patients still remained in hypocontractile state other 6 improved to normocontractile state. Two patients required timed voiding, double voiding and Clean Intermittent Self-Catheterization (CISC) up to this follow up period.Conclusions: After TURP, there were significant improvement of international prostate symptom score (IPSS), QoL, Urinary flow rate, serum creatinine, hydronephrosis and urodynamic parameters (PdetQmax, BCI, BOOI) and PVR among the patients of benign enlargement of prostate with chronic retention of urine. Though 25% patients of weak detrusor contractility failed to achieve normal contractility and needed timed voiding, double voiding and Clean Intermittent Self-Catheterization (CISC).Bangladesh J. Urol. 2025; 28(2): 60-66